Migration, ethnicity and mental health: evidence from mothers participating in the Millennium Cohort Study. (June 2019) - Moore, L.; Jayaweera, H.; Redshaw, M.; Quigley, M.
Abstract: Objectives: Over a quarter of UK births are to women who were born outside of the UK. Black and Minority Ethnic (BME) women are disproportionately affected by poor mental health and inequitable access to mental health care in the perinatal period, yet the influence of the migrant status (mothers' UK vs. non-UK birth) is poorly understood. This study aimed to explore the relationship between ethnicity, migration and mental health indicators among mothers participating in a large nationally representative cohort study. Study design: This is a secondary analysis of data from the Millennium Cohort Study. Methods: Logistic regression quantified the crude and adjusted effects of self-reported ethnicity and migrant status on prevalence of psychological distress and treatment for anxiety/depression at 9-month and 5-year postpartum. Results: We found substantial variation in the prevalence of distress according to ethnicity and migrant status, with Indian and Pakistani women at greatest risk. Despite equal or greater risk, BME and migrant women were less likely to report treatment for anxiety/depression. Mutually adjusted analyses showed ethnicity to be a stronger predictor of both outcomes than migrant status; however, at 5 years, being a migrant independently predicted lower odds of treatment, for a statistically similar level of distress. Conclusions: Migrant women are likely to be at high risk of poor mental health in the perinatal period and beyond, yet may face significant barriers to accessing mental health care. A better understanding of ethnicity and migration as interrelated risk factors for perinatal mental ill-health is needed to help National Health Service organisations develop policy and practice that is flexible and responsive to diversity. Highlights: Migrant and ethnic minority mothers are at increased risk of psychological distress. But are less likely than non-migrant/white British women to be treated for anxiety/depression. Ethnicity was a stronger predictor than migrant status of these differences.